2013
DOI: 10.1111/josh.12031
|View full text |Cite
|
Sign up to set email alerts
|

Physician Attitudes Regarding School‐Located Vaccination Clinics

Abstract: Pediatricians and family physicians expressed strong support of school vaccination clinics as sites for immunization delivery during outbreak situations but significantly less support for administering routine vaccinations. Increasing physician awareness of school-located vaccination clinic availability and establishing partnerships between physician practices and school vaccination clinics may improve access to immunizations for school-aged children and adolescents, particularly during large-scale communicabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…Research also shows that school-based vaccination is successful in reducing the burden of disease in the wider community as well as in the vaccinated population [4, 6, 7]. Studies have found school-based vaccination to be acceptable to education staff, health professionals, parents and students even when programmes involve new vaccines and parental concerns figure strongly [8, 9]. …”
Section: Introductionmentioning
confidence: 99%
“…Research also shows that school-based vaccination is successful in reducing the burden of disease in the wider community as well as in the vaccinated population [4, 6, 7]. Studies have found school-based vaccination to be acceptable to education staff, health professionals, parents and students even when programmes involve new vaccines and parental concerns figure strongly [8, 9]. …”
Section: Introductionmentioning
confidence: 99%
“…A growing body of research has found support for schools as a potential site to administer adolescent immunizations among health care professionals [19] and parents [19,20]. Leading professional and government organizations support providing vaccines in alternative settings [13,21], which has the potential to increase vaccination, particularly for those who are at risk of not receiving vaccines through the traditional medical home [22,23].…”
mentioning
confidence: 99%
“…Additionally, the school is conveniently located in a familiar and trusted community environment ( Klaiman et al, 2014 ). The school also offers a convenient option for parents to have their children receive needed vaccinations without having to arrange for a healthcare provider visit or take off time from work ( Fiala et al, 2013 ). The school nurse can play a critical role in planning a SLVE because of understanding both the needs of the community and the school.…”
Section: History and Review Of The Literaturementioning
confidence: 99%